2012
DOI: 10.1262/jrd.2011-010
|View full text |Cite
|
Sign up to set email alerts
|

Accumulated HSV1-TK Proteins Interfere with Spermatogenesis through a Disruption of the Integrity of Sertoli-Germ Cell Junctions

Abstract: Abstract. Transgenic rats show spermatid-specific ectopic expression of the reporter gene, herpes simplex virus type1 thymidine kinase (HSV1-TK), in the testes and have demonstrated male infertility. However, the disruption of spermatogenesis and the underlying molecular mechanisms in these transgenic animals have not been well clarified. In this study, light and electron microscopic observations were performed to characterize the morphological changes in the testes. To explore the molecular mechanisms of male… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 33 publications
1
8
0
Order By: Relevance
“…More recently, we demonstrated the possibility of Sertoli cell-germ cell disruption possibly by upregulation of Testin [6], the products of which play a crucial role in maintaining the junction between Sertoli cells and germ cells. Though the role of the HHV1-TK protein expressing thymidine kinase activity in the disruption of spermatogenesis is completely unclear at present, our cumulative data [1, 2, 6] certainly indicate a possibility that ectopic expression of infected HHV1 gene causes disruption of male gametogenesis. Elucidation of the molecular mechanism of the ectopic expression of HHV1-TK in round spermatid cells of the TG-rat is an important in vitro approach.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…More recently, we demonstrated the possibility of Sertoli cell-germ cell disruption possibly by upregulation of Testin [6], the products of which play a crucial role in maintaining the junction between Sertoli cells and germ cells. Though the role of the HHV1-TK protein expressing thymidine kinase activity in the disruption of spermatogenesis is completely unclear at present, our cumulative data [1, 2, 6] certainly indicate a possibility that ectopic expression of infected HHV1 gene causes disruption of male gametogenesis. Elucidation of the molecular mechanism of the ectopic expression of HHV1-TK in round spermatid cells of the TG-rat is an important in vitro approach.…”
Section: Discussionmentioning
confidence: 99%
“…We previously demonstrated that the transgenic rats show an ectopic expression and accumulation of HHV1-TK proteins in postmeiotic germ cells with disruption of spermatogenesis by the appearance of immature and abnormal sperm and age-dependent loss of germ cells via apoptotic cell death [2]. Continuous investigation by microarray and real-time PCR analyses revealed an increase in gene expression of Testin [6], a sensitive marker for monitoring the integrity of the Sertoli-germ cell junction. These results are suggestive and may provide a clue that may help uncover a relationship between virus infection and male infertility if the viral gene product(s) is expressed in the human male testis and causes male impairment of spermatogenesis.…”
mentioning
confidence: 99%
“…We sorted the genes by their functional categories, such as apoptosis, cell cycle, development, oxidative stress, proteolysis, signal transduction, transcription, translation, transport, metabolism, immune response, and cell adhesion. The highest number of affected genes was linked to metabolism, with 8 genes upregulated and 16 down-regulated by at least 1.5-fold in Tg rat testis ( Table 3) [42].…”
Section: Alterations In Gene Expression Profiles Of Tg Rat Testismentioning
confidence: 99%
“…Gene ontology classification of genes whose expression changes by at least .5-fold in Tg with respect to normal rats, as revealed by cDNA microarray analysis. Reproduced and modified from [42] with permission from the Society for Reproduction and Development. Notably, the contraceptive adjudin has been reported to induce morphological alterations in the seminiferous tubules similar to the ones we observed here, and target directly testin and actin-myosin [48].…”
Section: Alterations In Gene Expression Profiles Of Tg Rat Testismentioning
confidence: 99%
See 1 more Smart Citation